EKLESIOLOGI DIGITAL DI ERA PANDEMI DAN PASCA PANDEMI COVID-19 - Dani Firmanto Simanjuntak (Marturia, 2022)
AbstractDigital Ecclesiology is a concept that the author may offer to us (the church) as an effort to build a church that always exists, is strong and adaptive in the era of the pandemic and post-covid-19 pandemic. Our fellowship as a community of believers who come together (face to face) turns into a virtual community. Through digital technology, virtual space is an opportunity to meet other believers, as well as being interpreted as a space for spiritual encounters. In the historical series of ecclesiology in the Old Testament, New Testament, after the Reformation Period and until now, it is a sign for us that the church is constantly adapting to new cultures and phenomena. This Digital Ecclesiology means churches and ministries must move towards a more confident Digital Church than ever before. Churches globally must adapt quickly and innovatively to the challenges presented by the Covid-19 pandemic. Abstrak Eklesiologi Digital merupakan konsep yang boleh ditawarkan penulis bagi kita (gereja) sebagai upaya membangun gereja yang senantiasa eksis, kuat dan adaptif di era pandemi dan pasca pandemi covid-19. Persekutuan kita sebagai komunitas orang percaya yang berkumpul bersama (tatap muka) berubah menjadi komunitas virtual. Melalui teknologi digital, ruang virtual menjadi kesempatan bagi berjumpa dengan orang-orang percaya lainnya, sekaligus dapat dimaknai sebagai ruang perjumpaan spiritualitas. Dalam rentetan sejarah eklesiologi dalam Perjanjian Lama, Perjanjian Baru, Masa setelah Reformasi hingga saat ini menjadi pertanda bagi kita bahwa gereja senantiasa beradaptasi dengan budaya dan fenomena baru. Eklesiologi Digital ini berarti gereja dan pelayanan harus menuju ke Gereja Digital yang lebih percaya diri daripada sebelumnya. Gereja secara global harus beradaptasi dengan cepat dan inovatif terhadap tantangan yang dihadirkan oleh pandemi Covid-19.